Blood Biomarkers of Sensitization and Asthma - Sonntag, Hans-Joachim; Filippi, Sarah; Pipis, Spyros; Custovic, Adnan (Frontiers in Pediatrics, 2019)
Biomarkers are essential to determine different phenotypes of childhood asthma, and for the prediction of response to treatments. In young preschool children with asthma, aeroallergen sensitization and blood eosinophil count of 300/μL or greater may identify those who can benefit from the daily use of inhaled corticosteroids (ICS). We propose that every preschool child who is considered for ICS treatment should have these two features measured as a minimum before a decision is made on the commencement of long-term preventive treatment. In practice, IgE-mediated sensitization should be considered as a quantifiable variable, i.e. we should use the titre of sIgE antibodies or the size of skin prick test response. A number of other blood biomarkers may prove useful (e.g. allergen-specific IgG/IgE antibody ratios amongst sensitised individuals, component-resolved diagnostics which measures sIgE response to a large number of allergenic molecules, assessment of immune responses to viruses, level of serum CC16, etc), but it remains unclear whether these can be translated into clinically useful tests. Going forward, a more integrated approach which takes into account multiple domains of asthma, from the pattern of symptoms and blood biomarkers to genetic risk and lung function measures, is needed if we are to move towards a stratified approach to asthma management.